Cervical cancer screening behaviors among American Indian women: Cervical cancer literacy and health belief model. Issue 5 (3rd September 2021) - Lee, Yeon-Shim; Roh, Soonhee; Jun, Jung Sim; Goins, R. Turner; McKinley, Catherine E.
ABSTRACT: American Indian women experience disproportionately high rates of cervical cancer morbidity and mortality, yet cancer screening services tend to be underutilized. Using the Health Belief Model (HBM) with a survey of American Indian women ( N = 286) in South Dakota, findings indicate that only 59% received Pap test within the past 2 years. Significant predictors of Pap test included advanced age, higher BMI, greater awareness of Pap test, greater motivation, and lower barriers to screening. Findings highlight the importance of considering awareness of cancer screening and HBM constructs (barriers and motivation) in the examination of programs to improve screening among this population.